2010
DOI: 10.1021/es903576d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Propene Poisoning on Fe-ZSM-5 for Selective Catalytic Reduction of NOx with Ammonia

Abstract: Application of Fe-zeolites for urea-SCR of NO(x) in diesel engine is limited by catalyst deactivation with hydrocarbons. In this work, we investigated the effect of propene on the activity of Fe-ZSM-5 for selective catalytic reduction of NO(x) with ammonia (NH(3)-SCR), and proposed a deactivation mechanism of Fe(3+) active site blockage by propene residue. The NO conversion decreased in the presence of propene at various temperatures, while the effect was not significant when NO was replaced by NO(2) in the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
89
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 26 publications
7
89
0
Order By: Relevance
“…It is generally accepted that SCR process for Fe-Beta catalyst follows the dual site mechanism and the adsorption and activation of NH 3 is a crucial step. 31 Therefore, low acidity should be unfavorable for the NH 3 -SCR process.…”
Section: Nh 3 -Scr Performancesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally accepted that SCR process for Fe-Beta catalyst follows the dual site mechanism and the adsorption and activation of NH 3 is a crucial step. 31 Therefore, low acidity should be unfavorable for the NH 3 -SCR process.…”
Section: Nh 3 -Scr Performancesmentioning
confidence: 99%
“…Of course, as the core materials, the size of Beta crystal should be as small as possible. For shell materials, CeO 2 may be one of the most suitable metal oxides owing to its outstanding oxygen-storage capacity and easy conversion between Ce 31 and Ce 41 , which has been extensively used in various catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu and Fe have been the most widely used transition metal ions in NH 3 -SCR zeolite catalysts, owing to their good redox capacity [8,9]. Most of these catalysts show good NH 3 -SCR performance under high gas hourly space velocity (GHSV), which is crucial for their practical application in diesel vehicles with limited installation space on board [10][11][12]. Nowadays, diesel particulate filters (DPF) are widely used in diesel particulate emission control, and are often used in upstream of the SCR catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Fe-based catalysts such as Fe/ZSM-5 [7][8][9][10][11][12], Fe/HBEA [13][14][15][16], Fe-TiO 2 -PILC [17], Fe 2 O 3 /WO 3 /ZrO 2 [18] and Fe-Mn/USY [19] usually show good SCR activity and N 2 selectivity, and TiO 2 is usually used as support for SCR catalysts because of its high resistance to SO 2 poisoning [20]. Under the consideration to combine the merits of Fe active component and TiO 2 support, in our previous study [21][22][23] we reported a novel and environmental-friendly iron titanate catalyst FeTiO x prepared by co-precipitation method, showing high NH 3 -SCR activity, N 2 selectivity and H 2 O/SO 2 dura-bility in the medium temperature range (250-400 • C).…”
Section: Introductionmentioning
confidence: 99%